2014
DOI: 10.1016/j.compgeo.2013.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Case study and back analysis of a residential building damaged by expansive soils

Abstract: This paper presents a case study of a residential house damaged by expansive soils. The field investigation revealed that the damage was most likely caused by excessive lawn watering and leaks of sewer pipe and/or stormwater pipe, which resulted in non-uniform soil moisture conditions. Three-dimensional back analysis of this distressed structure indicated that stresses were most critical at a re-entrant corner and that steel reinforcing bars in the beam in this area had yielded. The results of the back analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(39 citation statements)
references
References 4 publications
1
38
0
Order By: Relevance
“…It expands when it absorbs more water and creates the potential to exert enough force on a building or other structures to cause damage. In addition, Tabuk city exposed too many flash floods, mainly from large drainage basin of Wadi Na'am, Al Baqqar and Dab'an which covered an area of about 2860 km 2 This study showed the importance of characterizing geotechnical properties and hydrological elements as part of a comprehensive environmental analysis for future urban planning. Based on the hazard map of the expansive soils of Tabuk city, it found that the western side of the city lying in the upstream of the small basin and the subsurface layers is composed of sandstone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It expands when it absorbs more water and creates the potential to exert enough force on a building or other structures to cause damage. In addition, Tabuk city exposed too many flash floods, mainly from large drainage basin of Wadi Na'am, Al Baqqar and Dab'an which covered an area of about 2860 km 2 This study showed the importance of characterizing geotechnical properties and hydrological elements as part of a comprehensive environmental analysis for future urban planning. Based on the hazard map of the expansive soils of Tabuk city, it found that the western side of the city lying in the upstream of the small basin and the subsurface layers is composed of sandstone.…”
Section: Discussionmentioning
confidence: 99%
“…Damages to infrastructure caused by expansi-ve soil movement have been widely reported in many countries such as Australia, China, United States, India and South Arica [2]. In America, the economic loss of the expansive soil question approximately amounts to above $15 billion every year [3] [4] [5] more than twice the damage from natural disasters.…”
Section: Introductionmentioning
confidence: 99%
“…At present, unsaturated soil mechanics is still relatively new in the geotechnical engineering field and there is little software available for simulating the fully coupled volume change behavior of expansive soils, let alone any well‐established program for simulating the fully coupled soil–foundation–structure system as proposed in the previous paper. As a result, as discussed in the previous sections, no one has yet been able to simulate all the factors influencing the behavior of residential buildings in a single program . By contrast, the fully coupled thermal stress analysis and the coupled thermal–mechanical interaction between deformable bodies have been investigated for a long time and there are many well‐established finite element method software packages such as ABAQUS and ANSYS.…”
Section: Simulation Of Movements Of Four Footings At Arlington Texasmentioning
confidence: 99%
“…The major limitation on past research simulating residential building on expansive soils is that the factors mentioned earlier have never been simultaneously investigated in a single analysis (e.g., [5,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]). The building, the foundation, and the soils make up the complete system.…”
Section: Assembly Of the Comprehensive Systemmentioning
confidence: 99%
See 1 more Smart Citation